Determining the Stable Injection Locking of a Fabry-Pérot Laser by Observing the RF Spectral Components Generated by a Low-Reflectivity External Cavity - Jakup Ratkoceri (MDPI AG, 2021)
A novel approach to monitoring the laser injection-locking (IL) state is proposed and verified using the side-mode suppression ratio (SMSR). In a photonics experiment for laser IL, an optical spectrum analyzer with the conventional criterion of a 35-dB SMSR is conventionally used to detect the locking state of a Fabry–Pérot (FP) laser with multiple longitudinal modes to an external master laser with one longitudinal mode. Since the 35-dB criterion is not always a sufficient locking condition, we propose a microwave-photonic technique to determine the stable-locking regime based on the observation of the radio-frequency (RF) components. A novel approach to monitoring the generated additional spectral components uses the well-known delayed-self-homodyne technique and the RF spectrum analyzer. For the novel generation of additional longitudinal groups on each FP laser’s resonator mode in the optical spectrum and consequently the overlapping RF components in the RF spectrum, an additional external resonator with low reflectivity was connected to the slave FP laser. The novel monitoring approach was experimentally verified by connecting a 1-m-long external cavity with 0.5% reflectivity and observing the optical IL phenomenon of a 1550-nm FP semiconductor laser.